The Effectiveness of Student-Centered Leadership Practices Of The Principal in Sekolah Berasrama Penuh Integrasi Tun Abdul Razak, Pahang : A Pilot Study - Suhaimi, Sharifuddin; A Ghani, Muhammad Faizal; Radzi, Norfariza Mohd (Proceedings Series of Educational Studies, 2024)
Effective leadership is vital in educational settings to foster a positive and productive school environment. Student-centered leadership, which emphasizes the needs, experiences, and voices of students in decision-making, is a key strategy for achieving this goal. This pilot study examines the effectiveness of student-centered leadership practices of the principal from the perspectives of students and teachers, focusing on key areas such as setting achievement targets, fostering high expectations, strategic resource planning, quality teaching practices, enhancing teacher competencies, and creating a conducive school environment. A quantitative survey method was employed, gathering responses from a total of 132 respondents, consisting of 96 students and 36 teachers, at Sekolah Berasrama Penuh Integrasi Tun Abdul Razak, Pahang. The survey, consisting of 30 items, demonstrated high reliability (Cronbach’s Alpha = 0.97). Data were analyzed using SPSS version 29.0 with descriptive statistics, including mean and standard deviation. Results indicate a high perceived effectiveness of student-centered leadership practices, with mean scores above 3.63 across all domains. Despite these positive outcomes, ongoing refinement and adaptation of leadership practices are essential to ensure sustained educational success.